NASCAR - Stevenson, Paul (Truro, Cornwall, UK : Hungry Tomato, 2024)
Get ready to discover the exciting world of NASCAR. With powerful cars, rapid racetracks, and spectacular crashes, NASCAR is a super-fast, super-tough sport. Check out the record-breaking heroes of NASCAR, and see if you've got what it takes to become a driver.
Includes index.
Keywords: NASCAR (Association) -- Juvenile literature; Automobile racing -- Juvenile literature